Short-term prediction of horizontal winds in the mesosphere and lower thermosphere over coastal Peru using a hybrid model - (:unkn) unknown (Frontiers Media S.A., 2024)
The mesosphere and lower thermosphere (MLT) are transitional regions between the lower and upper atmosphere. The MLT dynamics can be investigated using wind measurements conducted with meteor radars. Predicting MLT winds could help forecast ionospheric p...
Keywords: Predicción de vientos; Modelos híbridos